Composition for promoting lactation with tumour suppressive properties and preparation method thereof. - Mohamed, Suhaila; Shamsabadi, Fatemeh T.; Namvar, Farideh (2011)

(untitled)
The present invention discloses a nutraceutical composition alone or in combination with other biological active ingredients that is capable of increasing milk production and suppressing tumour in human and other mammals, the composition comprises marine algae, particularly seaweed plant extract having anti-estrogenic property. The seaweed plant derived nutraceutiacal either alone or in combination with other galactogogues, provides the necessary nutrients to increase milk production in mammmals.